Rutgers Boelens and Rosario Parra (2009) Rebel waters: Images of the struggle for water and justice in the Andes. A tribute to Julio García. Quito: IMPREFEPP: IEP - Lahud Vega, Julieta (2017)
The book Rebel waters: Images of the struggle for water and justice in the Andes. A tribute to Julio García, prepared by Rutgerd Boelens and Rosario Parra, provides an integrative vision on the dimension of water in peasant societies. It explores, among others, its meanings, conflicts and the emergence of the mercantilist logic of water. The authors propose "intercultural legality" as a mechanism for incorporating demands and recognition of assessments, management systems and local authorities.